2005
DOI: 10.1186/1471-2431-5-5
|View full text |Cite
|
Sign up to set email alerts
|

An exceptional Albanian family with seven children presenting with dysmorphic features and mental retardation: maternal phenylketonuria

Abstract: Background: Phenylketonuria is an inborn error of amino acid metabolism which can cause severe damage to the patient or, in the case of maternal phenylketonuria, to the foetus. The maternal phenylketonuria syndrome is caused by high blood phenylalanine concentrations during pregnancy and presents with serious foetal anomalies, especially congenital heart disease, microcephaly and mental retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Both dyspnea and perceived leg exertion were measured, but we report only Borg ratings for perceived leg exertion since our principal aim was modeling the stimulus‐response function. We employed the Dalhousie pictorial scales [ 11 ] and the Borg scale [ 12 ], chosen because it had been used in previous investigations in adults with similar aims [ 13 , 14 ]. Subjects were first given an explanation of the scale by the research assistant.…”
Section: Methodsmentioning
confidence: 99%
“…Both dyspnea and perceived leg exertion were measured, but we report only Borg ratings for perceived leg exertion since our principal aim was modeling the stimulus‐response function. We employed the Dalhousie pictorial scales [ 11 ] and the Borg scale [ 12 ], chosen because it had been used in previous investigations in adults with similar aims [ 13 , 14 ]. Subjects were first given an explanation of the scale by the research assistant.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 18 articles reporting pediatric DCRV were collected, 4,8-24 with 3 original articles, 4,8,15 1 case series; 18 and 14 case reports included. [9][10][11][12][13][14]16,17,[19][20][21][22][23][24] As a result, as many as 62 pediatric patients were recruited in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Nine (14.5%) patients had an isolated DCRV, 8,[13][14][15][16][18][19][20] and in 53 (85.5%) patients, the DCRV was associated with one or more congenital heart defects ( 2 =62.5, p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Three case reports described three women who were diagnosed with PKU only after a pregnancy with MPKU embryopathy; although one was intellectually delayed, the other two were described as completely normal. [27][28][29] Additionally, Plana et al, reported 4 women who were unaware that they were affected by PKU but all had mild intellectual defects and two of the mothers had classical PKU phenotypes. 30 We reported a 32-year-old intellectually normal female who was found to have classical PKU in the course of duo exome sequencing performed because of a history of recurrent pregnancy loss and early neonatal deaths with malformations including brain anomalies and congenital heart defect.…”
Section: Discussionmentioning
confidence: 99%